EFEKTIVITAS PENGELOLAAN KINERJA PEGAWAI DAN EMPLOYEE ENGAGEMENT DALAM HUBUNGANNYA DENGAN KINERJA PEGAWAI - Setyawasih, Rianti; Budiyono, Haris (Fakultas Ekonomi Universitas Islam 45, 2017)
This article explains on how effective performance management and employee engagement are likely to have an important and unique influence on high employee performance. The result shows that effective performance management has directly and indirectly influence on employee performance and directly influence employee engagement, it also was proved that employee engagement has directly influence on employee performance. Then, to produce some employee performance increments may be best achieved by integrating employee engagement to the performance management system at the organization. Employees who are engaged in their work and committed to their organizations give companies crucial competitive advantages, including higher productivity and lower employee turnover.  To this end, a new approach is introduced to the performance management process that includes employee engagement and the key drivers of employee engagement at each stage of performance management.